Вычисление функций Бесселя с помощью непрерывных дробей - Валеев, К.Г.; Костинский, О.Я. (Український математичний журнал, 1995)
Запропоновано новий спосіб обчислення функцій Бесселя першого роду цілого порядку. За допомогою перетворення Лапласа розв’язується лінійне диференціальне рівняння, яке визначає твірну функцій Бесселя, що виражаються через неперервні дроби. We propose a new method for the calculation of Bessel functions of the first kind of integral order. By using the Laplace transformation, we solve a linear differential equation that defines the generating function for the Bessel functions expressed in terms of continued fractions.